AB0607 SELF-MANAGEMENT BEHAVIOURS IN ANCA-ASSOCIATED VASCULITIS: SECONDARY ANALYSIS OF INTERVIEW DATA. (June 2019) - Reynolds, Tim; Dures, Emma; Ashdown, Sue; Cronholm, Peter; Luqmani, Raashid; Merkel, Peter; Milman, Nataliya; Peck, Jacqueline; Robson, Joanna
Abstract : Background: ANCA-associated vasculitis (AAV) is a significant cause of morbidity and mortality. Meeting the challenges of aAV effectively requires patients to engage in self-management, including medical management, role management, and emotional management. 1 Self-management is recognised as a key aspect of chronic disease management and forms an important part of the National Health Service 5-year forward plan and the UK strategy for rare diseases. 2, 3 Nonetheless, there has been limited specific research into the role of self-management in the aAV literature. Objectives: To explore experiences and views of self-management amongst aAV patients. Methods: A secondary analysis of all interview transcripts from a previous project exploring health-related quality of life in relation to aAV was performed. 4 Deductive analysis was used to map appropriate areas discussed by patients to the self-management framework proposed by Lorig and Holman. 1 inductive analysis was used to identify emergent themes that did not fit into this framework. Results: Interview data were collected from 50 patients with aAV (25 men), from the UK (n=18), USA (n=17) and Canada (n=15). Diagnoses included GPA (n=26), EGPA (n=17) and MPA (n=7). Thirty-four patients were diagnosed within the last 2 years and 16 were diagnosed more than 2 years ago. 4 From the core tasks proposed in Lorig and Holman's framework, patients with aAV appear to attribute particular importance to maintaining life roles and to a lesser extent medication management and dealing with the emotions of chronic disease. Core skills necessary to self-manage in aAV include learning to take action as part of self-efficacy, forming productive health-care partnerships, learning about decision making (requiring disease and self-awareness), utilising resources effectively, and problem-solving. Three themes emerged that were not included in Lorig and Holman's framework that respondents related to self-management abilities including: 1) support received from family, support groups, and religion; 2) the influence of pre-morbid personality factors; 3) the role patients attributed to developing a foundation of specific aAV knowledge in their subsequent ability to self-manage. Conclusion: Patients with aAV self-manage in a variety of ways and their needs may change over time. Patients may benefit from support to help manage changing life roles and to deal with the challenges of having a chronic disease. Over time, support may need to shift focus onto core skills including recognising when to take action; forming effective partnerships with healthcare providers, family, and friends; adaptations to day-to-day changes in their condition; utilising resources appropriately; and strategies for problem-solving. References: [1] Lorig, K.R. And Holman, H.R., 2003. Self-management education: history, definition, outcomes, and mechanisms. Annals of behavioral medicine, 26(1), pp.1-7. [2] NHS England. Five year forward view. Oct2014. Available from:https://www.england.nhs.uk/ourwork/futurenhs/ [3] UK Strategy for Rare Diseases. Department of Health, 2013. [4] Robson, J.C., Dawson, J., Cronholm, P.F., Milman, N., Kellom, K.S., ashdown, S., Easley, E., Farrar, J.T., Gebhart, D., Lanier, G. AndMcAlear, C.A., 2018. Health-related quality of life in aNCA-associated vasculitis and item generation for a disease-specific patient-reported outcome measure. Patient related outcome measures, 9, p.17. Disclosure of interests: Tim Reynolds: None declared, Emma Dures Grant/research support from: Has previously received an independent learning grant from Pfizer, however the work has been completed and the grant has been closed., Sue ashdown: None declared, Peter Cronholm: None declared, Raashid Luqmani Grant/research support from: Roche, Vifor and GSK, Peter Merkel: None declared, Nataliya Milman: None declared, Jacqueline Peck: None declared, Joanna Robson: None declared